PENINGKATAN PENETRASI NATRIUM ASKORBIL FOSFAT MENGGUNAKAN SISTEM NIOSOM SPAN 80 DALAM SEDIAAN GEL SECARA IN VITRO - ., Vivi Amelia Citra Dewi (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2015)
Sodium ascorbyl phosphate (NAF) is the derivative of vitamin C, commonly used in cosmetic field as an antioxidant. NAF has a partition coefficient -4 and hydrophiliccoumpound which makes it diffucult to pass through the stratum corneum. Therefore,niosome system span 80 as an appropriate carrier system is needed. This research aims toinvestigate the increase in penetration of sodium ascorbyl phosphate using the systemniosome span 80 in the preparation of the gel in vitro. Concentration of span 80 was variedinto three formulas : formula 1 (100µmol), formula 2 (200µmol) dan formula 3(300µmol).Niosome was made by using thin layer hydration method and test was conducted on theefficiency of entrapment, stability testing of gel readiness and penetration by in vitro test.Entrapment efficiency test method used dialysis.The suspensi niosomes was formulated in theform of gel readiness using basic gel of viscolam MAC 10 8%. The stability tests wereperformed for 28 days. Penetration test performed by in vitro test using shed snake skinmembrane. The entrapment efficiency result showed the most optimum span 80 concentrationis the F1 (100μmol) of 98,7665% ± 0,0587. The results showed that the niosome system NAFhas the best stability compared with NAF gel without niosome organoleptic, pH anddetermination of levels. The penetration test result for 8 hours showed that NAF niosome gelcan diffuse about 82,6565% ± 0,0378.  Keywords: Niosome, Sodium Ascorbyl Phosphate, Span 80, Penetration by in vitro test